KAJIAN IN SILICOPOTENSI DAN KEAMANAN PEPTIDA TURUNAN ?-GLIADIN SEBAGAI PEPTIDA PENEMBUS SEL - Chairunnisa Muharroro, Hanifa
Generally, the challenges of delivering biopharmaceutical compounds orally are the low permeability and instability under gastrointestinal conditions. One approach that can be taken to overcome the permeability problem is the use of Cell Penetrating Peptides (CPP). CPP comprises 5- 30 amino acids with the ability to penetrate cell membranes. CPP can be derived from natural proteins, one of which is ?-gliadin Triticum monococcum. Gliadin is a prolamin-rich protein from wheat with resistance to the gastrointestinal tract and mucoadhesive properties. This research conducted in silico prediction of the potency and safety of a peptide derived from gliadin as CPP. Gliadin was digested using PeptideCutter program to result in 128 peptides. Their potential as CPP were predicted using CellPPD web. A total of 26 CPP candidates were selected based on peptide length criteria and exclusion of tetrapeptide toxic motifs. The safety of the CPP candidates were predicted using ToxinPred and ToxDL for toxicity, ANTIGENpro and Ellipro for antigenicity, as well as AllergenFP, and AllerTOP v.2 for allergenicity. The non-conforming prediction results were evaluated using analysis employing decoy peptides. The results show peptides with the sequence QIPEQSQCQAIHNVVHAII (p177-195) as the relatively safest CPP candidates. The p177-195 structure was modeled with PEP-FOLD3 and its position in the whole ?-gliadin structure was predicted. After analyzing its structure and physicochemical properties, p177-195 was predicted as an anionic amphipathic class of CPP with a hydrophobic tendency.